Successful Treatment with Clonazepam and Pramipexole of a Patient with Sleep-Related Eating Disorder Associated with Restless Legs Syndrome: A Case Report. (14th March 2012) - Kobayashi, Nobuyuki; Yoshimura, Ryohei; Takano, Masahiro
Abstract : Sleep-related eating disorder (SRED) is characterized by recurrent episodes of involuntary eating during sleep period and is often associated with restless legs syndrome (RLS). Although pharmacotherapy is recommended for SRED patients, no drug have shown promising effects so far. The patient, a 48-year-old Japanese housewife, first visited our clinic and complained about nighttime eating. She had a history of hypertension, diabetes mellitus, sleep apnea syndrome, and depression. Insomnia appeared 10 years before the first visit and she often received hypnosedatives; at the same time, she developed nocturnal eating episodes. She had amnesia for these episodes, and she felt urge to move her legs while sleeping. The patient was diagnosed with SRED and RLS. Reduction in the doses of triazolam decreased her nighttime eating frequency, and her complete amnesia changed to vague recall of eating during night. Clonazepam 1.0 mg at bedtime decreased nocturnal eating frequency from 1 to 2 times per month, though sleepwalking remained. Administration of pramipexole 0.125 mg relieved all symptoms including SRED, RLS, and sleepwalking. This is the first paper to report that the combination of clonazepam and pramipexole therapy-reduced SRED episodes and RLS symptoms.